Expression of aif, parp, and mirnas mir-145, mir-210, and mir-486 associated with apoptosis in the corpus cavernosum of rats subjected to chronic alcoholism model - Sarraipo, Vagner Schiavoni (2020)
SUMMARY: Previous studies from our group described the consequences of using ethanol on penile erection. Nevertheless, the molecular mechanisms surrounding microRNAs, apoptosis process and their relationship with erectile dysfunction associated with alcohol consumption are still poorly understood. The objective of this analysis was to evaluate the mechanism of apoptosis by the expression of AIF and PARP, as well as their regulatory microRNAs: miR-145, miR-210 and miR-486, in the corpus cavernosum of rats submitted to a semivoluntary alcoholism model. For this study 24 Wistar rats were divided into two groups: control (C) and treated with 20 % ethanol (A) for seven weeks. The corpus cavernosum samples were prepared for immunohistochemical analysis of AIF and PARP protein expression, and microRNAs miR-145, miR-210, miR-486 gene expression in cavernous tissue was performed by real time PCR. The immunohistochemical analysis showed little nuclear positive labeling for the protein PARP and AIF in the corpus cavernosum of control and ethanol treated animals. After analysis of miR-145,-210 and-486 microRNA expression in the 12 animals studied, no results were found with significant statistical difference between the control and alcoholized groups. The expression of AIF and PARP and their regulatory microRNAs involved in apoptotic process (miR-145, miR-210 and miR-486) were not altered in the corpus cavernosum of rats submitted to semivoluntary alcoholism.